The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41467-020-15076-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate adaptation by crop migration

Abstract: Many studies have estimated the adverse effects of climate change on crop yields, however, this literature almost universally assumes a constant geographic distribution of crops in the future. Movement of growing areas to limit exposure to adverse climate conditions has been discussed as a theoretical adaptive response but has not previously been quantified or demonstrated at a global scale. Here, we assess how changes in rainfed crop area have already mediated growing season temperature trends for rainfed mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(136 citation statements)
references
References 61 publications
3
127
0
6
Order By: Relevance
“…A number of world regions currently rely heavily on rain-fed agriculture and require abundant irrigation, which has increased cultivation costs and raised conflicts over access to water. This situation has promoted unwanted environmental problems arising from quantity and quality changes in soil and water (Thiery et al, 2020;Sloat et al, 2020;Dai et al, 2020). A few studies have addressed the effects of global warming on agricultural water use including changes in net irrigation, water demand and water uptake by crops.…”
Section: Increased Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of world regions currently rely heavily on rain-fed agriculture and require abundant irrigation, which has increased cultivation costs and raised conflicts over access to water. This situation has promoted unwanted environmental problems arising from quantity and quality changes in soil and water (Thiery et al, 2020;Sloat et al, 2020;Dai et al, 2020). A few studies have addressed the effects of global warming on agricultural water use including changes in net irrigation, water demand and water uptake by crops.…”
Section: Increased Irrigationmentioning
confidence: 99%
“…Climate projections have been used to estimate water demand for future irrigation (Gondim et al, 2012;Bakken et al, 2016), which are estimated to increase between 40 and 250% depending on the crop at the end of this century. The increased requirements have been ascribed to reduce water availability in the growing seasons, evapotranspiration and changes in crop phenology (Woznicki et al, 2015;Sloat et al, 2020;Dai et al, 2020). This causes great uncertainty about the predictions in the literature (Chung and Nkomozepi, 2012).…”
Section: Increased Irrigationmentioning
confidence: 99%
“…Resilience to unpredictable weather will also benefit from intercropping, with the creative arrangement of multiple interacting crop species to diversify the field and the landscape 101,172,285,286 . Sloat et al 287 reported that warming impact on maize, wheat and rice could be moderated by migration of these crops over time and the expansion of irrigation. Multiple-cropping systems and strategies to integrate animals and crops will make more efficient use of natural resources and applied inputs; these include systems such as permaculture, agroforestry, alley cropping, intercropping and sowing C 4 crops compared to C 3 crops.…”
Section: Plant Breeding and Genetic Modifications Plant Breeding Andmentioning
confidence: 99%
“…Breeding should be aimed at improving the varieties' drought tolerance, deep rooting of the root system [8,38,39], and creating cold-resistant early varieties that can be planted early in order to avoid the risks of drought in the second half of summer [9]. Climate warming creates the prerequisites for the advance of soybean varieties to the more northern regions with better precipitation [40].…”
Section: Discussionmentioning
confidence: 99%